Haplotype Analysis of Candidate Genes Involved in Inflammation and Oxidative Stress and the Susceptibility to Preeclampsia. (26th February 2020) - Chen, Aiping; Zhao, Huifang; Wang, Jingli; Zhang, Ru; Liu, Jingjing; Zhao, Xin; Li, Congying; Jia, Xuewen; Li, Xueying; Lin, Yan; Guo, Mingzhen; Li, Sai; et al.
Abstract : Unbalanced inflammatory reactions and oxidative stress are inseparably interconnected, and both may play crucial roles in the pathophysiological mechanisms of preeclampsia (PE). In the published previous studies, we have genotyped for SNPs that related to inflammation (rs2227485, rs153109, rs17855750, rs2027432, rs2275913, rs763780, rs4819554, and rs13015714) and oxidative stress (rs1695, rs4680, rs1800566, rs4807542, rs713041, rs7579, rs230813, rs1004467, rs3824755, and rs9932581) to investigate whether these polymorphisms were associated with susceptibility to PE in a Chinese Han population. In this present study, we collected these data of experimental and clinical from above studies for haplotype analysis of inflammation-related SNPs in 631 PE patients and 720 normal pregnancy and oxidative stress-related SNPs in 342 PE patients and 457 normal pregnancies for susceptibility to PE. The data of genotype distribution and allele frequency comparisons after correction for multiple comparisons (P/8 or P/10) showed 2 among the 8 candidate inflammation-related SNPs have significant differences (rs2027432 genotype χ 2 = 407.377, p < 0.001, p < 0.00625 ). Moreover, the minor alleles of rs2027432 T (minor   allele   χ 2 = 450.923, p < 0.001, p < 0.00625 ; OR = 21.439, 95 % CI = 15.181 ‐ 30.278 ) and rs4819554 G (minor   allele   χ 2 = 163.465, p < 0.001, p < 0.00625 ; OR = 5.814, 95 % CI = 4.380 ‐ 7.719 ) were confirmed as risk allele of PE, respectively. Our analysis revealed rs2027432 (TT) of NLRP3 and rs4819554 (GG) of IL-17RA are risk factors for PE. However, no significant difference was found at the oxidative stress-related SNPs. In the candidate loci for oxidative stress, we also identified 3 SNP matches (rs4807542 and rs713041, rs230813 and rs75799, rs1004467 and rs3824755) that had high linkage disequilibrium (LD) with each other and were selected as a block (r 2 = 0.98, r 2 = 0.97, r 2 = 0.97, r 2 > 0.9 ), and the GT and GC haplotypes of rs4807542 and rs713041 in GPX4 showed significant differences between the PE and control groups (χ 2 = 5.143, p = 0.0233, p < 0.05 ; χ 2 = 6.373, p = 0.0116, p < 0.05 ). So, we inferred that polymorphisms of NLRP3 rs2027432 and IL-17RA rs4819554, which are related to inflammation, and the rs713041 variant of GPX4, which is related to oxidative stress, were associated with susceptibility to PE. The GT and GC haplotypes of rs4807542 and rs713041 in GPX4 may increase the risk of PE in the Chinese Han population.